Hemodynamic versus adrenergic control of cat right ventricular hypertrophy. - Cooper, G (1985)
The purpose of this study was to determine whether cardiac hypertrophy in response to hemodynamic overloading is a primary result of the increased load or is instead a secondary result of such other factors as concurrent sympathetic activation. To make this distinction, four experiments were done; the major experimental result, cardiac hypertrophy, was assessed in terms of ventricular mass and cardiocyte cross-sectional area. In the first experiment, the cat right ventricle was loaded differentially by pressure overloading the ventricle, while unloading a constituent papillary muscle; this model was used to ask whether any endogenous or exogenous substance caused uniform hypertrophy, or whether locally appropriate load responses caused ventricular hypertrophy with papillary muscle atrophy. The latter result obtained, both when each aspect of differential loading was simultaneous and when a previously hypertrophied papillary muscle was unloaded in a pressure overloaded right ventricle. In the second experiment, epicardial denervation and then pressure overloading was used to assess the role of local neurogenic catecholamines in the genesis of hypertrophy. The degree of hypertrophy caused by these procedures was the same as that caused by pressure overloading alone. In the third and fourth experiments, beta-adrenoceptor or alpha-adrenoceptor blockade was produced before and maintained during pressure overloading. The hypertrophic response did not differ in either case from that caused by pressure overloading without adrenoceptor blockade. These experiments demonstrate the following: first, cardiac hypertrophy is a local response to increased load, so that any factor serving as a mediator of this response must be either locally generated or selectively active only in those cardiocytes in which stress and/or strain are increased; second, catecholamines are not that mediator, in that adrenergic activation is neither necessary for nor importantly modifies the cardiac hypertrophic response to an increased hemodynamic load.